The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1676-0611-bn-2016-0174
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyofauna of Mundaú river basin, Ceará State, Northeastern Brazil

Abstract: Mundaú river basin is located at Center-North Ceará State and occupies a total area of 2,227 km2, including Estuário do Rio Mundaú Environmental Protection Area. This study aimed to catalog the fishes of this basin. Collections were performed with active and passive gear in 35 sampling sites, between 2012 and 2014, in several habitats (main channels, streams, floodplains, permanent and temporary pools, ponds, and dams). A total of 2,545 specimens were collected, belonging to 55 species distributed in 10 orders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
12
0
1
Order By: Relevance
“…Hemigrammus rodwayi has been reported for streams in Guiana, Suriname, French Guiana and the Amazon basin (Reis et al 2003, Buckup et al 2007) with few reported records for the northeastern Brazil (Teixeira et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hemigrammus rodwayi has been reported for streams in Guiana, Suriname, French Guiana and the Amazon basin (Reis et al 2003, Buckup et al 2007) with few reported records for the northeastern Brazil (Teixeira et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm has recently changed with the publication of a book chapter entitled "Diversity, patterns of distribution and conservation of fishes from Caatinga" in Rosa et al (2003) listed 240 species of freshwater fishes for the Caatinga biome, comprising the broadest evaluation about the freshwater ichthyofauna from this region to date. Various studies have since been undertaken which the understanding of the regional ichthyofauna through publications, including: Ramos et al (2005), Alves et al (2008), Nascimento et al (2011), Cardoso (2012), Gurgel-Lourenço et al (2013), Novaes et al (2013, Camelier & Zanata (2014), Nascimento et al (2014), Paiva et al (2014), Silva et al (2014), Ramos et al (2014), Silva et al (2015), Gurgel-Lourenço et al (2015), Rodrigues-Filho et al (2016), Costa et al (2017), Teixeira et al (2017) and Oliveira-Silva et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed integrative analysis using both molecular and morphological data, including more specimens, especially males, may confirm the identity of the species from the Mundaú river basin. Moreover, the occurrence of the critically endangered non-annual rivulid, Anablepsoides cearensis (Costa & Vono, 2009) in the coastal plains of this basin (Teixeira et al 2017, ICMBio 2018 corroborates it as an extremely high priority area for the Caatinga's fish conservation (MMA 2018).…”
Section: Resultsmentioning
confidence: 81%